2020
DOI: 10.1088/1755-1315/497/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon sequestration at different age of tea [Camelia sinensis] plantation under the wet tropical area

Abstract: Soil organic carbon [OC] sequestration is affected by some factors, one of which is the vegetation living on it. Tea is a crop on which the part being harvested is the leaves, which are supposed to contribute to soil OC. The objective of the research was to determine the amount of OC sequestered at different crop age under tea plantation in wet tropical areas. The soil samples were taken from 3 different crop ages [36, 21, and 9 years old] under the same slope [>45%] and soil [volcanic] at ≥ 1,400 m asl. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…It could improve or worsen soil behavior. Land-use change from forest to corn cultivation reduced SOM stock by 128% under Inceptisols and 14% under Oxisols in Lima Puluh Kota, the tropical area (Yulnafatmawita et al 2020). However, Yulnafatmawita et al (2020) reported land-use conversion from the forest into tea plantation in volcanic soil in Batang Barus dan Gunung Talang, Solok Regency, increased SOM stock and improved soil physical properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It could improve or worsen soil behavior. Land-use change from forest to corn cultivation reduced SOM stock by 128% under Inceptisols and 14% under Oxisols in Lima Puluh Kota, the tropical area (Yulnafatmawita et al 2020). However, Yulnafatmawita et al (2020) reported land-use conversion from the forest into tea plantation in volcanic soil in Batang Barus dan Gunung Talang, Solok Regency, increased SOM stock and improved soil physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Land-use change from forest to corn cultivation reduced SOM stock by 128% under Inceptisols and 14% under Oxisols in Lima Puluh Kota, the tropical area (Yulnafatmawita et al 2020). However, Yulnafatmawita et al (2020) reported land-use conversion from the forest into tea plantation in volcanic soil in Batang Barus dan Gunung Talang, Solok Regency, increased SOM stock and improved soil physical properties. Landuse change from forest to others in recently developed soil in the east part of Maninjau caldera was studied to determine the effect on soil physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [10] reported that tea plantation in the Aie Batumbuak, Gunung Talang District was planted on sloping area (>100% slope). However, there were no visible signs of erosion on the ground surface, and no landslide hazard had ever been there.…”
Section: Introductionmentioning
confidence: 99%
“…Land conversion will change the amount and quality of OM contributed to the soil. Yulnafatmawita et al [10] reported that land-use changes from secondary forest to tea plantations in Gunung Talang District were able to increase the OM content of the soil. Furthermore, Tumwebaze and Byakagaba [13] stated that the coffee agroforestry system could be a method to improve OM accumulation in the terrestrial to minimize global warming.…”
Section: Introductionmentioning
confidence: 99%